Design of a six-speed transmission hub with an integrated brushless permanent-magnet motor used for electric bicycles. Issue 2 (25th February 2014) - Wu, Yi-Chang; Lin, Bo-Wei
Abstract : Purpose: – The electric motor and multi-speed transmission hub are essential components for an electric bicycle. Traditionally, these two devices have been designed and manufactured independently. The purpose of this study is to propose a novel electromechanical device that artfully integrates an exterior-rotor brushless permanent-magnet (BLPM) motor into a transmission hub to become a compact structural assembly. Design/methodology/approach: – A novel design that integrates a three-phase, 20-pole/18-slot exterior-rotor BLPM motor with a multi-speed transmission hub composed of a six-link, two-degrees-of-freedom (2-DOF) compound planetary gear train (PGT) is presented in this study to overcome inherent drawbacks of existing designs. An analytical approach, based on fundamental circuits, is developed to synthesize the clutching sequences and numbers of teeth of all gears of the PGT. Findings: – The integrated device provides six forward speeds, including two underdrives, two direct drives, and two overdrives, as well as two drive modes: the motor-drive mode and the human-drive mode, for electric bicycles. The main feature of the proposed design is the spur gear teeth merged with the pole shoes of the stator to dramatically minimize the detent torque, which is an oscillatory torque that always induces vibration and acoustic noise of the BLPM motor. Originality/value: – The gear teeth on the pole shoes of the stator provide functions not only for transmission, but also act as dummy slots for adjusting the magnetostatic field of the BLPM motor to effectively reduce the detent torque. The peak value of the detent torque of the integrated design is only 9 percent of the original BLPM motor with identical magnet properties and motor dimensions. Such a feature is contributive in suppressing the vibration and acoustic noise of the electric bicycle's BLPM motor. A BLPM motor rated at 310 W and 250 r/min for the integrated device is presented and analyzed by using the commercial finite-element package Ansoft/Maxwell 2D Field Simulator.